Penerapan Model Pembelajaran Kooperatif Tipe STAD (Student Team Achievement Division) untuk Meningkatkan Aktivitas dan Hasil Belajar Matematika Siswa - Ni Putu Widiastuti; Putu Sanjaya; I Ketut Suparya (Edukasi: Jurnal Pendidikan Dasar, 2020)
This study aims to determine the application of the STAD type cooperative learning model can improve mathematics learning activities and outcomes in fifth grade students of SD Negeri 2 Tista in the academic year 2019/2020. Based on the results of the study, it can be explained that the average percentage of mathematics learning activities in prasiklus reached 37.18%, the average percentage of mathematics learning outcomes reached 64.18% and classical completeness reached 47.06%. After applying the STAD type cooperative learning model in the first cycle the average percentage of student learning activities increased to 58.82%, the average percentage of learning outcomes reached 74.47% and classical completeness reached 74.47%. With the improvement in cycle II the average percentage of learning activities increased to 80.08%, the average percentage of student learning outcomes increased to 82.35% and classical completeness reached 100%. Keywords: STAD type cooperative model, activities, learning outcomes